Helicobacter pylori and cancer among adults in Uganda. - Newton, R; Ziegler, J; Casabonne, D; Carpenter, L; Gold, B; Owens, M; Beral, V; Mbidde, E; Parkin, D; Wabinga, H; Mbulaiteye, S; Jaffe, H (2006)
Data from Africa on infection with Helicobacter pylori (H. pylori) are sparse. Therefore, as part of an epidemiological study of cancer in Uganda, we investigated the prevalence and determinants of antibodies against H. pylori among 854 people with different cancer types and benign tumours. Patients were recruited from hospitals in Kampala, Uganda, interviewed about various demographic and lifestyle factors and tested for antibodies against H. pylori. In all patients combined, excluding those with stomach cancer (which has been associated with H. pylori infection), the prevalence of antibodies was 87% (723/833) overall, but declined with increasing age (p = 0.02) and was lower among people who were HIV seropositive compared to seronegative (p < 0.001). Otherwise, there were few consistent epidemiological associations. Among those with stomach cancer, 18/21 (86%) had anti-H. pylori antibodies (odds ratio 0.8, 95% confidence intervals 0.2-2.9, p = 0.7; estimated using all other patients as controls, with adjustment for age, sex and HIV serostatus). No other cancer site or type was significantly associated with anti-H. pylori antibodies. The prevalence of H. pylori reported here is broadly in accord with results from other developing countries, although the determinants of infection and its' role in the aetiology of gastric cancer in Uganda remain unclear.